OLD POETRY OF KOREAN SOCIETY - Kim Suzie; Kim Sunwoo; Jinhee Woo; Agus Sulaeman (STIBA IEC JAKARTA, 2023)
The purpose of this study is to describe the structure of old Korean poetry. This study uses qualitative research methods as one of the methods to achieve the goal of content analysis. A qualitative research document draws conclusions based on the quality of directly observed data rather than the quantity of measured data. As a qualitative research method, it is a research method that uses the wealth of experience and intuitive views of researchers to obtain in-depth and detailed information about research subjects. In collecting data, researchers used content analysis techniques from collections of old Korean poetry. This research studied old poetry of Korean classic songs which were the subject of study. Old poetry of Korean classical songs, among them, <Cheoyongga>, which Korean students study and are widely known when they are in junior high and high school, <Gujiga>, <Anminga>, <Changiparanga>, <Saeyasaeya parangsaeya>, and <Jindallaekkot> total 6. From the results of the study, it was obtained descriptions of the roles, meanings, and values of Korean classical songs in society in the past. In terms of Korean classic songs that have been passed down to the present day, this is very valuable data because it contains past life and customs before the natural modern era and contains people's thoughts at that time, including images of the time. Since, researchers conduct research in the form of collecting and analyzing data rather than digitizing it, approach it in a descriptive way.